Perancangan Sistem Informasi Pengarsipan Surat Berbasis Web Di UPT SMPN 34 Gresik - Ananda Hafiz Syawala; Farhanna Mar`i (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
One of the educational institutions that is involved in managing correspondence is UPT SMPN 34 Gresik. Because UPT SMPN 34 Gresik still applies manual accounting methods, it requires a lot of paper for recording and as a result there is a buildup of archival data. Researchers propose the use of a MySQL database and a design process to create a web-based letter filing system to overcome these problems. Fall out. After this research is completed, a web-based letter filing system will be developed at UPT SMPN 34 Gresik with the aim of increasing efficiency, speeding up the archiving process, and ensuring accurate and safe document storage. The web-based technology letter filing system is expected to simplify administrative tasks and improve school policy and human resource management, based on insights from observation, interview and literature study methodologies. The aim of this research is to be able to provide UPT SMPN 34 Gresik with comprehensive and long-term answers to its demands.